Perancangan Aplikasi Manajemen Keanggotaan dan Keuangan Berbasis Web pada GKRI Efesus - Adhi, Dennis Kurniawan; Tony, Tony (STMIK Banjarbaru, 2024)
Gereja Kristus Rahmani Indonesia Efesus (GKRI Efesus) church serves the congregation through various worship activities, such as general worship, youth, commune, and Sunday school. To support smooth administration, the church needs an efficient data management system, especially in terms of membership management managed by the membership admin as the church secretary. GKRI Efesus has a financial system for recording collection money, tithes, donations, and expenses. The web-based management application will be built using PHP, Laravel framework, and Bootstrap to ensure ease of use and access on various devices. A MySQL database is used to store membership data in a secure and structured manner, making the recording of member information more efficient. This application was developed using the SCRUM method so that each stage can be adjusted to user needs. This application is expected to support the church in managing data effectively thus the administrators can focus more on services and spiritual growth of the congregation. Blackbox testing results show that the features of the membership and financial information system application have functioned as needed, including login, data management, and dashboards. Keywords: Management; Church; Membership; LaravelÂ AbstrakGKRI Efesus melayani jemaat melalui berbagai kegiatan ibadah, seperti ibadah umum, pemuda, komsel, dan sekolah minggu. Untuk mendukung kelancaran administrasi, Gereja membutuhkan sistem manajemen data yang efisien, terutama dalam hal pengelolaan keanggotaan yang dikelola oleh admin keanggotaan sebagai sekretaris Gereja. GKRI Efesus juga memiliki sistem keuangan untuk pencatatan uang kolekte, perpuluhan, sumbangan, dan pengeluaran. Aplikasi manajemen berbasis web akan dibangun menggunakan PHP, framework Laravel, dan Bootstrap untuk memastikan kemudahan penggunaan dan akses di berbagai perangkat. Database MySQL digunakan untuk menyimpan data keanggotaan secara aman dan terstruktur sehingga pencatatan informasi anggota lebih efisien. Aplikasi ini dikembangkan menggunakan metode SCRUM agar setiap tahapannya bisa disesuaikan dengan kebutuhan pengguna. Hasil pengujian Blackbox Testing menunjukkan fitur aplikasi sistem informasi keanggotaan dan keuangan telah berfungsi sesuai kebutuhan, termasuk login, pengelolaan data, dan dashboard.Â